2019
DOI: 10.1016/j.physletb.2018.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Sea quark Sivers distribution

Abstract: We compute sea quark Sivers distribution within color glass condensate(CGC) framework. It has been found that up to the leading logarithm accuracy, the collinear twist-3 approach and the CGC calculation yield the same result for sea quark Sivers distribution in the dilute limit. We further verify that transverse momentum dependent factorization is consistent with CGC treatment at small x for the case of transverse spin asymmetry in open charm quark production in semi-inclusive deeply inelastic scattering proce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 87 publications
7
18
0
Order By: Relevance
“…Similar conclusion of the odderon dominance in the small-x quark Sivers function was reached in [3] using the expression for the small-x unpolarized quark TMD (unintegrated quark distribution) from [94,99] (see also [23,100]). While qualitatively our result and that in [3] agree on the odderon-driven quark Sivers TMD, a more detailed comparison between the two calculations is left for future work. The importance of C-odd correlators in the Sivers asymmetry was also pointed out in [101,102].…”
Section: Jhep11(2021)200supporting
confidence: 65%
See 2 more Smart Citations
“…Similar conclusion of the odderon dominance in the small-x quark Sivers function was reached in [3] using the expression for the small-x unpolarized quark TMD (unintegrated quark distribution) from [94,99] (see also [23,100]). While qualitatively our result and that in [3] agree on the odderon-driven quark Sivers TMD, a more detailed comparison between the two calculations is left for future work. The importance of C-odd correlators in the Sivers asymmetry was also pointed out in [101,102].…”
Section: Jhep11(2021)200supporting
confidence: 65%
“…Indeed, in [5] the odderon was shown to generate single transverse spin asymmetry for the quark jet production in scattering of a quark on a transversely polarized nucleon, further suggesting the odderon's connection with the quark Sivers function. Moreover, recently, in [3] it was shown that the spin-dependent odderon does contribute to the quark Sivers function. In this work we study the intersection of these diverse areas of QCD by constructing the small-x asymptotics of the quark Sivers function.…”
Section: Jhep11(2021)200mentioning
confidence: 99%
See 1 more Smart Citation
“…2.8. Recent theoretical study suggested an opposite sign between the strange quark and anti-strange quark Sivers functions [82] apart from the sign-flip prediction of the Sivers functions probed in SIDIS and Drell-Yan processes. The experimental test of this prediction at EicC will enrich our knowledge about the proton spin structure, particularly in the relatively small x region.…”
Section: Fig 27mentioning
confidence: 95%
“…Yet, the exact treatment of the problem has been difficult due to the lack of a systematic way to connect the Pomeron and Odderon with the spin degrees of freedom of the scattering (composite) particles such as protons in QCD. 1 Recently, however, there has been a significant progress in our understanding of the interplay between the Odderon and the proton spin [29][30][31][32][33][34]. In the Deep Inelastic Scattering (DIS) at small-x, the Color Glass Condensate (CGC) framework [35] provides a consistent description of the Pomeron and Odderon in terms of Wilson line correlators.…”
Section: Introductionmentioning
confidence: 99%